The VARIATION OF MICROWAVE POWER AND CONCENTRATION OF BUTTERFLY PEA FLOWER IN ANTOCHIANIN EXTRACTION USING MAE METHOD - Putri, Audika; Muttaqin, M. Ayib; Muyassaroh, Muyassaroh; Hudha, Mohammad Istnaeny (jurnal ATMOSPHERE, 2026)
Butterfly pea flower (Clitoria ternatea) contains anthocyanins, flavonoid pigments with antioxidant activity and potential as natural colorants and herbs. Anthocyanin extraction via Microwave Assisted Extraction (MAE) offers rapid extraction, reduced solvent use, and high efficiency. This study evaluated the effect of microwave power and solid-to-solvent ratio on anthocyanin extraction using ethanol acidified with 3.5% citric acid. Extractions were conducted at 100, 200, 300, and 399 W with ratios of 1:10, 1:15, 1:20, and 1:25. Extraction performance was assessed based on yield and anthocyanin content. The highest yield (18.44%) was obtained at 100 W and a 1:25 ratio, while the highest anthocyanin content (29.2 mg/100 g) was achieved at 399 W and a 1:10 ratio. The optimal condition was 300 W and a 1:20 ratio, providing a balanced extraction performance between yield and anthocyanin content.